Analisis Strategi Manajemen Kesehatan dalam Memaksimalkan Mutu Pelayanan di Rumah Sakit: Literature Review - Wasiyem Wasiyem; Amanda Dwika; Wulan Dwi Citra Sari; Fani Rulinanda Ritonga; Salsabilla Julinda Sumpeno; Rani Ramadhani; Maharani Zahra; Rahayu Sri Rezeki Kandau; Zahra Andini (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
The quality of health services in hospitals is the main indicator in evaluating the effectiveness of the health management system. This study aims to analyze various health management strategies applied in hospitals to maximize service quality through a literature review approach. The strategies identified include digital transformation, human resource (HR) development, the implementation of kaizen culture, and the optimization of hospital management information systems (SIMRS). A literature review shows that technology-based approaches, HR training, and data-driven management play an important role in improving efficiency, patient satisfaction, and service safety. However, challenges such as limited infrastructure, resistance to change, and large investment needs remain obstacles. This study concludes that the integration of holistic and adaptive management strategies is necessary to achieve optimal service quality in hospitals.